All-solid-state lithium metal battery interface protection layer and preparation method and application thereof

By using the interface protective layer with gradient conductivity in all-solid lithium metal batteries, the problem of poor battery cycle stability and safety is solved, and the uniform deposition of lithium and the uniformization of electric field are achieved, which significantly improves the cycle stability of the battery and security.

CN119419389AActive Publication Date: 2025-02-11CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411633831.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-11
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The deliquency/lithium embeddedness of all-solid-state lithium metal batteries during the circulation process is low, resulting in poor circulation stability and safety, hindering their widespread application.

Method used

An all-solid-state lithium metal battery interface protection layer is adopted, which has gradient conductivity. By mixing the solid electrolyte Li6PS5Cl with conductive carbon or lithium-philic element M and uniformly dispersing it, an interface protection layer with a single-layer or multi-layer structure is constructed. , to achieve uniform deposition of lithium and electric field homogenization.

Benefits of technology

It effectively improves the cycle stability and safety of all-solid lithium metal batteries, and extends the battery's service life and reduces safety risks through uniform lithium deposition and suppresses side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419389A_ABST
    Figure CN119419389A_ABST
Patent Text Reader

Abstract

The invention provides an all-solid-state lithium metal battery interface protection layer and a preparation method and application thereof, and belongs to the technical field of negative electrode materials in all-solid-state battery systems, and the interface protection layer is of a single-layer structure or a multi-layer structure; the single-layer structure is composed of Li6PS5Cl and conductive carbon, and the mass ratio of the Li6PS5Cl to the conductive carbon is any one of 99.5: 0.5, 99: 1, 97: 3 and 95: 5; or the single-layer structure is composed of Li6PS5Cl and a lithium-loving element M, and the mass ratio of the Li6PS5Cl to the lithium-loving element M is 75: 25; the multi-layer structure is formed by stacking a plurality of interface layers, each interface layer is composed of Li6PS5Cl and conductive carbon, and the mass ratio of the Li6PS5Cl to the conductive carbon is any one of 99.5: 0.5, 99: 1, 97: 3 and 95: 5; and in the plurality of interface layers, the content of the conductive carbon is gradually increased layer by layer. The interface protection layer has gradient conductivity, so that uniform deposition of lithium is effectively induced while ion and electron transmission in the all-solid-state lithium metal battery is ensured, and the cycling stability and safety of the all-solid-state lithium metal battery are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials in all-solid-state battery systems, and in particular relates to an all-solid-state lithium metal battery interface protection layer and a preparation method and application thereof. Background Art

[0002] Since the advent of commercial lithium-ion batteries in the 1990s, they have had a profound impact on our society over the past 30 years. However, the energy density of commercial batteries is currently limited to about 300 Wh kg. -1 , and cannot fully meet the ever-increasing energy storage needs of contemporary society in terms of consumer electronics and electric vehicle endurance. The use of metallic lithium negative electrodes is critical to significantly increase the energy density of batteries. Due to some inherent problems of lithium metal batteries, the lithium removal / insertion efficiency (Coulomb efficiency) of lithium metal during the cycle process is reduced. The main reasons are the growth of lithium dendrites during the cycle, side reactions between electrolytes and electrodes, and the generation of dead lithium, which greatly reduces the cycle stability and safety of all-solid-state lithium metal batteries, seriously hindering the widespread application of all-solid-state lithium metal batteries. Summary of the invention

[0003] In order to solve the problems of poor cycle stability and safety of existing all-solid-state lithium metal batteries, the present invention provides an all-solid-state lithium metal battery interface protection layer, which has gradient conductivity, and effectively induces uniform deposition of lithium while ensuring the internal ion and electron transmission of the all-solid-state lithium metal battery, thereby improving the cycle stability and safety of the all-solid-state lithium metal battery.

[0004] The present invention also provides a method for preparing an interface protection layer for an all-solid-state lithium metal battery and an application thereof.

[0005] The present invention is achieved through the following technical solutions:

[0006] The present invention provides an interface protection layer for an all-solid-state lithium metal battery, wherein the interface protection layer is a single-layer structure or a multi-layer structure;

[0007] The single-layer structure is composed of Li6PS5Cl and conductive carbon, and the mass ratio of Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5;

[0008] Alternatively, the single-layer structure is composed of Li6PS5Cl and a lithium-philic element M, and the mass ratio of Li6PS5Cl to the lithium-philic element M is 75:25;

[0009] The multilayer structure is formed by stacking several interface layers, the interface layer is composed of Li6PS5Cl and conductive carbon, and the mass ratio of Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5;

[0010] In the several interface layers, the content of the conductive carbon increases layer by layer.

[0011] Optionally, the thickness of the interface protection layer is 5 to 200 μm.

[0012] Optionally, the conductive carbon includes at least one of graphite, Super P, carbon nanotubes, carbon black and Ketjen black;

[0013] The lithium-philic element M is at least one of Cu, Zn, Mg, Al, Sb, Ca, Ba, Ag, In, Bi, Ge, B and Sn.

[0014] Based on the same inventive concept, the present invention provides a method for preparing an interface protective layer of an all-solid-state lithium metal battery, the preparation method comprising:

[0015] The solid electrolyte Li6PS5Cl and the conductive carbon are mixed and ground under an inert atmosphere to obtain a mixture A, wherein the mass ratio of the Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5;

[0016] Alternatively, the solid electrolyte Li6PS5Cl and the lithium-philic element M are mixed in a mass ratio of 75:25 under an inert atmosphere and then ground to obtain a mixture B;

[0017] coating or depositing the mixture A or the mixture B on the surface of a substrate to obtain a single-layer structure;

[0018] Alternatively, a plurality of the mixtures A having different conductive carbon contents are coated or deposited layer by layer on the substrate surface in order from low to high conductive carbon contents to obtain a multilayer structure.

[0019] Furthermore, the particle size of the particles in the mixture A is 1 to 5 μm;

[0020] The particle size of the particles in the mixture B is 1 to 5 μm;

[0021] The conductive carbon comprises at least one of graphite, Super P, carbon nanotubes, carbon black and Ketjen black;

[0022] The lithium-philic element M is at least one of Cu, Zn, Mg, Al, Sb, Ca, Ba, Ag, In, Bi, Ge, B and Sn.

[0023] Furthermore, coating or depositing the mixture A or the mixture B on the surface of a substrate to obtain a single-layer structure specifically includes:

[0024] The mixture A or the mixture B is coated on the surface of a substrate, and then a pressure of 300 to 500 MPa is applied to obtain a single-layer structure;

[0025] Alternatively, the mixture A or the mixture B is attached to the surface of a substrate by atomic layer deposition to obtain a single-layer structure;

[0026] The method of coating or depositing the plurality of mixtures A with different conductive carbon contents on the substrate surface layer by layer according to the conductive carbon contents from low to high to obtain a multilayer structure specifically includes:

[0027] The plurality of mixtures A having different conductive carbon contents are coated layer by layer on the surface of the substrate according to the conductive carbon content from low to high, and then a pressure of 300 to 500 MPa is applied to obtain a multilayer structure;

[0028] Alternatively, a plurality of the mixtures A having different conductive carbon contents are deposited layer by layer on the substrate surface in order from low to high conductive carbon contents to obtain a multilayer structure.

[0029] Based on the same inventive concept, the present invention provides an electrolyte-gradient conductive interface protection layer-lithium metal structure, wherein the electrolyte-gradient conductive interface protection layer-lithium metal structure comprises an electrolyte sheet, a lithium foil and the above-mentioned all-solid-state lithium metal battery interface protection layer;

[0030] The electrolyte sheet and the lithium foil are respectively attached to two sides of the interface protection layer;

[0031] When the interface protection layer is a multi-layer structure, the side of the multi-layer structure with a high conductive carbon content is attached to the lithium foil.

[0032] Based on the same inventive concept, the present invention provides a method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure, the preparation method comprising:

[0033] The solid electrolyte Li6PS5Cl and the conductive carbon are mixed and ground under an inert atmosphere to obtain a mixture A, wherein the mass ratio of the Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5;

[0034] Alternatively, the solid electrolyte Li6PS5Cl and the lithium-philic element M are mixed in a mass ratio of 75:25 under an inert atmosphere and then ground to obtain a mixture B;

[0035] The solid electrolyte Li6PS5Cl is pressed into an electrolyte sheet in a battery mold;

[0036] The mixture A is coated or deposited on one side or both sides of the electrolyte sheet, and pressed to fit with the lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure;

[0037] Alternatively, a plurality of the mixtures A with different conductive carbon contents are coated or deposited layer by layer on one or both sides of the electrolyte sheet according to the conductive carbon contents from low to high, and pressed and laminated with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure;

[0038] Alternatively, the mixture B is coated or deposited on one or both sides of the electrolyte sheet, pressed and laminated with lithium foil, and then allowed to stand at 60±1° C. for 12±0.5 h to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure.

[0039] Furthermore, the particle size of the particles in the mixture A is 1 to 5 μm;

[0040] The particle size of the particles in the mixture B is 1 to 5 μm;

[0041] The thickness of the electrolyte sheet is 800-900 μm;

[0042] The conductive carbon comprises at least one of graphite, Super P, carbon nanotubes, carbon black and Ketjen black;

[0043] The lithium-philic element M is at least one of Cu, Zn, Mg, Al, Sb, Ca, Ba, Ag, In, Bi, Ge, B and Sn.

[0044] Furthermore, the mixture A is coated or deposited on one side or both sides of the electrolyte sheet, and pressed and laminated with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure, which specifically includes:

[0045] The mixture A is coated or deposited on one side or both sides of the electrolyte sheet, and then a pressure of 300-500 MPa is applied, and then a pressure of 5-10 MPa is applied to laminate with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure;

[0046] The method comprises coating or depositing the plurality of mixtures A with different conductive carbon contents on one side or both sides of the electrolyte sheet layer by layer according to the conductive carbon contents from low to high, and laminating the electrolyte sheet with the lithium foil under pressure to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure, specifically comprising:

[0047] The plurality of mixtures A with different conductive carbon contents are coated or deposited layer by layer on one side or both sides of the electrolyte sheet according to the conductive carbon content from low to high, and then a pressure of 300-500 MPa is applied, and then a pressure of 5-10 MPa is applied to laminate with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure;

[0048] The mixture B is coated or deposited on one side or both sides of the electrolyte sheet, pressed and laminated with lithium foil, and then left to stand at 60±1° C. for 12±0.5 h to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure, specifically comprising:

[0049] The mixture B is coated or deposited on one or both sides of the electrolyte sheet, and then a pressure of 300-500 MPa is applied, and then a pressure of 5-10 MPa is applied to fit the lithium foil, and then the mixture is allowed to stand at 60±1°C for 12±0.5 h to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure.

[0050] Based on the same inventive concept, the present invention provides an electrolyte-gradient conductive interface protection layer structure, wherein the electrolyte-gradient conductive interface protection layer structure comprises an electrolyte sheet and the above-mentioned all-solid-state lithium metal battery interface protection layer;

[0051] The interface protection layer is attached to one side of the electrolyte sheet;

[0052] When the interface protection layer is a multi-layer structure, the side of the multi-layer structure with a low conductive carbon content is attached to the electrolyte sheet.

[0053] Based on the same inventive concept, the present invention provides an application of an all-solid-state lithium metal battery interface protection layer in the preparation of an all-solid-state lithium metal battery.

[0054] Based on the same inventive concept, the present invention provides an application of an electrolyte-gradient conductive interface protection layer-lithium metal structure in the preparation of an all-solid-state lithium metal battery.

[0055] Based on the same inventive concept, the present invention also provides an application of an electrolyte-gradient conductive interface protection layer structure in the preparation of an all-solid-state lithium metal battery.

[0056] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0057] 1. The present invention discloses an interface protection layer for an all-solid-state lithium metal battery. The interface protection layer is obtained by mixing a solid electrolyte with conductive carbon or a lithium-philic element M and uniformly dispersing the mixture, and coating and pressurizing the mixture to obtain an interface protection layer with gradient conductivity. The interface protection layer with a single-layer or multi-layer structure can achieve gradient conductivity and can be used as an intermediate layer between the solid electrolyte and the lithium metal negative electrode. The lithium-philic element M can spontaneously diffuse to the lithium metal side at high temperature to achieve the same purpose, thereby realizing the construction of an interface protection layer between the solid electrolyte and the lithium metal. There is a certain difference in conductivity between the conductive carbon and the electrolyte and the lithium metal, and the conductive carbon is mainly used to achieve electric field homogenization. The interface protection layer can not only reduce the local current density and induce uniform lithium deposition, but also improve the adhesion between the lithium deposition layer and the negative electrode, thereby forming a solid electrolyte interface layer with good mechanical properties and uniform flux, effectively inhibiting the side reaction between the deposited lithium and the electrolyte, and thus improving the cycle stability and safety of the all-solid-state lithium metal battery.

[0058] 2. The present invention discloses an electrolyte-gradient conductive interface protection layer-lithium metal structure. By uniformly dispersing the electrolyte and the conductive carbon / lithium-philic element M, an interface layer with gradient conductive properties is obtained, and an electrolyte-gradient conductive interface protection layer-lithium metal / lithium-free negative electrode structure is constructed to take into account both structural stability and high electrochemical properties. The electrolyte Li6PS5Cl has the characteristics of lithium repellency and electrochemical inertness, and has ultra-high stability during the lithium insertion / deinsertion process. The difference in electronic conductivity of the interface layer constructed by the electrolyte + conductive carbon / lithium-philic element M can not only ensure electron transmission, but also effectively induce the uniform nucleation process of metallic lithium on the interface layer, thereby ultimately improving the battery performance.

[0059] 3. The present invention provides an electrolyte-gradient conductive interface protection layer-lithium metal structure, in which the electrolyte Li6PS5Cl has high electrochemical performance and structural stability, and maintains a highly stable skeleton structure while achieving rapid ion migration. The conductive interface layer with different gradients can effectively induce a uniform deposition process of lithium while ensuring the internal ion and electron transmission, and ultimately achieve the purpose of rapid diffusion of lithium ions to the negative electrode side and uniform deposition. In addition, the solid electrolyte and lithium metal of the present invention both have a high lithium ion diffusion coefficient and a high lithium ion transport capacity, which helps to improve the uniform diffusion of lithium ions into the interface layer in terms of kinetic characteristics, thereby achieving more uniform metal lithium deposition and ultimately improving battery performance.

[0060] 4. The present invention provides a method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure. The method can simply and effectively inhibit the growth of lithium dendrites by constructing an interface protection layer intermediate layer with certain gradient conductive properties between the solid electrolyte and the lithium metal negative electrode side. The process of the present invention is simple and easy to industrially apply. The design of the electrolyte-gradient conductive interface protection layer-lithium metal / lithium-free negative electrode structure takes into account the structural stability and high electrochemical performance when subsequently applied to batteries, meeting the requirements of commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0062] Figure 1 It is a schematic diagram of the all-solid-state battery electrolyte-gradient conductive interface protection layer-lithium metal / lithium-free negative electrode structure of the present invention.

[0063] Figure 2 These are the SEM and EDS images of the cross-section of the all-solid-state battery electrolyte-gradient conductive interface protection layer-lithium metal structure of Example 1.

[0064] Figure 3 The figure is a comparison chart of the battery cycle performance between Example 1 and Comparative Example 1.

[0065] Figure 4 The figure is a comparison chart of the battery cycle performance between Example 2 and Comparative Example 1.

[0066] Figure 5 The figure is a comparison chart of the battery cycle performance between Example 3 and Comparative Example 1.

[0067] Figure numerals: 1-electrolyte, 2-gradient conductive interface protection layer, 3-lithium metal / lithium-free negative electrode. DETAILED DESCRIPTION

[0068] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0069] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0070] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0071] The technical principle of the present invention is as follows:

[0072] The present invention provides an interface protection layer for an all-solid-state lithium metal battery, wherein the interface protection layer is a single-layer structure or a multi-layer structure;

[0073] The single-layer structure is composed of Li6PS5Cl and conductive carbon, and the mass ratio of Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5;

[0074] Alternatively, the single-layer structure is composed of Li6PS5Cl and a lithium-philic element M, and the mass ratio of Li6PS5Cl to the lithium-philic element M is 75:25;

[0075] The multilayer structure is formed by stacking several interface layers, the interface layer is composed of Li6PS5Cl and conductive carbon, and the mass ratio of Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5;

[0076] In the several interface layers, the content of the conductive carbon increases layer by layer.

[0077] In the present invention, the mass ratio of Li6PS5Cl to conductive carbon is selected from 99.5:0.5, 99:1, 97:3 and 95:5, which has the advantage of effectively changing the electronic conduction of the interface layer without affecting the ion conduction; the mass ratio of Li6PS5Cl to the lithium-philic element M is 75:25, which can effectively change the electronic conduction of the interface layer without affecting the ion conduction.

[0078] Optionally, the thickness of the interface protection layer is 5 to 200 μm.

[0079] In the present invention, the thickness of the interface protection layer is 5 to 200 μm, which has the advantage of reducing the influence on ion transmission.

[0080] In the present invention, the addition of conductive carbon and lithium-philic element M mainly plays a role in changing the conductivity of the interface layer, constructing a gradient conductive interface, thereby homogenizing the interface electric field, achieving uniform lithium deposition, and inhibiting the deposition and growth of lithium dendrites.

[0081] Optionally, the conductive carbon includes at least one of graphite, Super P, carbon nanotubes, carbon black and Ketjen black;

[0082] The lithium-philic element M is at least one of Cu, Zn, Mg, Al, Sb, Ca, Ba, Ag, In, Bi, Ge, B and Sn.

[0083] Based on the same inventive concept, the present invention provides an electrolyte-gradient conductive interface protection layer-lithium metal structure, wherein the electrolyte-gradient conductive interface protection layer-lithium metal structure comprises an electrolyte sheet, a lithium foil and the above-mentioned all-solid-state lithium metal battery interface protection layer;

[0084] The electrolyte sheet and the lithium foil are respectively attached to two sides of the interface protection layer;

[0085] When the interface protection layer is a multi-layer structure, the side of the multi-layer structure with a high conductive carbon content is attached to the lithium foil.

[0086] In the present invention, the advantage of laminating the side with high conductive carbon content in the multilayer structure with the lithium foil is that a gradient conductive interface is effectively formed to reduce interface impedance.

[0087] Based on the same inventive concept, the present invention provides a method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure, the preparation method comprising:

[0088] The solid electrolyte Li6PS5Cl and the conductive carbon are mixed and ground under an inert atmosphere to obtain a mixture A, wherein the mass ratio of the Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5;

[0089] Alternatively, the solid electrolyte Li6PS5Cl and the lithium-philic element M are mixed in a mass ratio of 75:25 under an inert atmosphere and then ground to obtain a mixture B;

[0090] The solid electrolyte Li6PS5Cl is pressed into an electrolyte sheet in a battery mold;

[0091] The mixture A is coated or deposited on one side or both sides of the electrolyte sheet, and pressed to fit with the lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure;

[0092] Alternatively, a plurality of the mixtures A with different conductive carbon contents are coated or deposited layer by layer on one or both sides of the electrolyte sheet according to the conductive carbon contents from low to high, and pressed and laminated with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure;

[0093] Alternatively, the mixture B is coated or deposited on one or both sides of the electrolyte sheet, pressed and laminated with lithium foil, and then allowed to stand at 60±1° C. for 12±0.5 h to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure.

[0094] In the present invention, the mixture B is coated or deposited on one or both sides of the electrolyte sheet, laminated with the lithium foil after pressurization, and then left to stand at 60±1°C for 12±0.5 h. The benefit is that the lithium-philic metal M can effectively and spontaneously migrate to the lithium metal to form a conductive gradient difference.

[0095] Furthermore, the particle size of the particles in the mixture A is 1 to 5 μm;

[0096] The particle size of the particles in the mixture B is 1 to 5 μm;

[0097] The thickness of the electrolyte sheet is 800-900 μm;

[0098] The conductive carbon comprises at least one of graphite, Super P, carbon nanotubes, carbon black and Ketjen black;

[0099] The lithium-philic element M is at least one of Cu, Zn, Mg, Al, Sb, Ca, Ba, Ag, In, Bi, Ge, B and Sn.

[0100] In the present invention, the particle size of the mixture A and B is 1 to 5 μm, which has the advantage of effectively improving the density of the electrolyte and interface layer material particles and improving the ion transport of the material.

[0101] Furthermore, the mixture A is coated or deposited on one side or both sides of the electrolyte sheet, and pressed and laminated with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure, which specifically includes:

[0102] The mixture A is coated or deposited on one side or both sides of the electrolyte sheet, and then a pressure of 300-500 MPa is applied, and then a pressure of 5-10 MPa is applied to laminate with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure;

[0103] The method comprises coating or depositing the plurality of mixtures A with different conductive carbon contents on one side or both sides of the electrolyte sheet layer by layer according to the conductive carbon contents from low to high, and laminating the electrolyte sheet with the lithium foil under pressure to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure, specifically comprising:

[0104] The plurality of mixtures A with different conductive carbon contents are coated or deposited layer by layer on one side or both sides of the electrolyte sheet according to the conductive carbon content from low to high, and then a pressure of 300-500 MPa is applied, and then a pressure of 5-10 MPa is applied to laminate with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure;

[0105] The mixture B is coated or deposited on one side or both sides of the electrolyte sheet, pressed and laminated with lithium foil, and then left to stand at 60±1° C. for 12±0.5 h to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure, specifically comprising:

[0106] The mixture B is coated or deposited on one or both sides of the electrolyte sheet, and then a pressure of 300-500 MPa is applied, and then a pressure of 5-10 MPa is applied to fit the lithium foil, and then the mixture is allowed to stand at 60±1°C for 12±0.5 h to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure.

[0107] In the present invention, applying a pressure of 5 to 10 MPa has the advantage of reducing the interface impedance and improving the contact between the lithium metal and the interface layer. Too low a pressure may easily lead to poor contact between the lithium metal and the interface layer.

[0108] In the present invention, the solid electrolyte Li6PS5Cl can be other solid electrolytes with relatively high lithium ion diffusion coefficient and electrochemical stability with lithium metal.

[0109] Based on the same inventive concept, the present invention provides an electrolyte-gradient conductive interface protection layer structure, wherein the electrolyte-gradient conductive interface protection layer structure comprises an electrolyte sheet and the above-mentioned all-solid-state lithium metal battery interface protection layer;

[0110] The interface protection layer is attached to one side of the electrolyte sheet;

[0111] When the interface protection layer is a multi-layer structure, the side of the multi-layer structure with a low conductive carbon content is attached to the electrolyte sheet.

[0112] In the present invention, the electrolyte-gradient conductive interface protection layer structure is also called electrolyte-gradient conductive interface protection layer-lithium-free negative electrode structure, which can reduce the application of lithium metal, allow lithium to be directly deposited on one side of the current collector, and further inhibit the growth of lithium dendrites.

[0113] The following will describe in detail an all-solid-state lithium metal battery interface protection layer, a preparation method and an application thereof in combination with embodiments and experimental data.

[0114] Example 1

[0115] This embodiment provides a method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure:

[0116] Step 1: The solid electrolyte Li6PS5Cl and Super P are mixed in an agate mortar / ball mill at a mass ratio of 99:1 under an Ar atmosphere, and fully ground for 30 minutes to make them uniform. The particle size of the obtained mixture is 1 to 5 μm.

[0117] Step 2: Press Li6PS5Cl into a thin sheet (i.e., an electrolyte sheet with a thickness of 800 μm) in a battery mold, then add the mixture in step 1 to one side of the sheet and pressurize (500 MPa) to obtain a 40 μm thick interface layer, and finally attach lithium foil to this side and pressurize 10 MPa to improve the contact, thereby obtaining an electrolyte-gradient conductive interface protection layer-lithium metal structure.

[0118] Battery assembly: Based on the above structure, the positive electrode LiNi is added to the other side of the electrolyte sheet Li6PS5Cl 0.89 Co 0.06 Mn 0.05 O2 is assembled into an all-solid-state battery; alternatively, the same electrolyte-gradient conductive interface protection layer-lithium metal structure is constructed on the other side of the electrolyte sheet, that is, assembled into a lithium metal symmetric battery.

[0119] Comparative Example 1

[0120] Li6PS5Cl is used as electrolyte and LiNi 0.89 Co 0.06 Mn 0.05 O2 is used as the positive electrode and lithium foil is used as the negative electrode to assemble full batteries and lithium symmetrical batteries.

[0121] Example 2

[0122] This embodiment provides a method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure:

[0123] Step 1: The solid electrolyte Li6PS5Cl and Super P are mixed in an agate mortar / ball mill in an Ar atmosphere at a mass ratio of 99.5:0.5 and 97:3, respectively, and fully ground for 30 minutes to make it uniform. The particle size of the obtained mixture is 1 to 5 μm.

[0124] Step 2: Press Li6PS5Cl into a thin sheet with a thickness of 800 μm in a battery mold, apply a mixture with a mass ratio of 99.5-0.5% in step 1 on one side of the thin sheet and pressurize (300 MPa) to obtain a 20 μm thick coating, then apply a mixture with a mass ratio of 97-3% and pressurize (500 MPa) to obtain a 20 μm thick coating to obtain an interface layer with a total thickness of 40 μm, finally apply lithium foil and pressurize at 10 MPa to improve contact, thereby obtaining an electrolyte-gradient conductive interface protection layer-lithium metal structure.

[0125] Battery assembly: Based on the above structure, the positive electrode LiNi is added to the other side of the electrolyte sheet Li6PS5Cl 0.89 Co 0.06 Mn 0.05O2 is assembled into an all-solid-state lithium metal battery, or, the same electrolyte-gradient conductive interface protection layer-lithium metal structure is constructed on the other side of the electrolyte sheet, that is, assembled into a lithium metal symmetric battery.

[0126] Example 3

[0127] This embodiment provides a method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure:

[0128] Step 1: Solid electrolyte Li6PS5Cl and Mg are mixed in an agate mortar / ball mill in an Ar atmosphere at a mass ratio of 75:25, and fully ground for 30 minutes to make them uniform. The particle size of the obtained mixture is 1 to 5 μm.

[0129] Step 2: Li6PS5Cl is pressed into a thin sheet with a thickness of 800 μm in a battery mold, and then the mixture in step 1 is added to one side of the thin sheet and pressurized (500 MPa). Finally, lithium foil is attached to this side and pressurized at 10 MPa at 60 °C for 12 hours to obtain a 30 μm thick interface layer, that is, an electrolyte-gradient conductive interface protection layer-lithium metal structure.

[0130] Battery assembly: Based on the above structure, the positive electrode LiNi is added to the other side of the electrolyte sheet Li6PS5Cl 0.89 Co 0.06 Mn 0.05 O2 is assembled into an all-solid-state lithium metal battery, or, the same electrolyte-gradient conductive interface protection layer-lithium metal structure is constructed on the other side of the electrolyte sheet Li6PS5Cl, that is, assembled into a lithium metal symmetric battery.

[0131] Example 4

[0132] This embodiment provides a method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure:

[0133] Step 1: The solid electrolyte Li6PS5Cl and Super P are mixed in an agate mortar / ball mill in an Ar atmosphere at a mass ratio of 99.5:0.5 and 97:3, respectively, and fully ground for 30 minutes to make it uniform. The particle size of the obtained mixture is 1 to 5 μm.

[0134] Step 2: Press Li6PS5Cl into a thin sheet with a thickness of 800 μm in a battery mold, then add the mixtures with a mass ratio of 99.5:0.5 and 97:3 in step 1 into the atomic layer deposition equipment and deposit them on one side of the thin sheet, with a thickness of 20 μm, to obtain an interface layer with a total thickness of 40 μm. Finally, attach lithium foil to this side and apply a pressure of 10 MPa to improve the contact, thereby obtaining an electrolyte-gradient conductive interface protection layer-lithium metal structure.

[0135] Battery assembly: Based on the above structure, the positive electrode LiNi is added to the other side of the electrolyte sheet Li6PS5Cl 0.89 Co 0.06 Mn 0.05 O2 is assembled into an all-solid-state lithium metal battery, or, the same electrolyte-gradient conductive interface protection layer-lithium metal structure is constructed on the other side of the electrolyte sheet Li6PS5Cl, that is, assembled into a lithium metal symmetric battery.

[0136] Example 5

[0137] This embodiment provides a method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure:

[0138] Step 1: Solid electrolyte Li6PS5Cl and Mg are mixed in an agate mortar / ball mill in an Ar atmosphere at a mass ratio of 75:25, and fully ground for 30 minutes to make them uniform. The particle size of the obtained mixture is 1 to 5 μm.

[0139] Step 2: Li6PS5Cl is pressed into a thin sheet with a thickness of 800 μm in a battery mold, and then the mixture in step 1 is added to one side of the thin sheet in an atomic layer deposition device and deposited. Finally, lithium foil is attached to the side and pressurized at 10 MPa at 60 °C and left to stand for 12 hours to obtain a 30 μm interface layer, that is, an electrolyte-gradient conductive interface protection layer-lithium metal structure.

[0140] Battery assembly: Based on the above structure, a positive electrode LiNi is added to the other side of the electrolyte Li6PS5Cl 0.89 Co 0.06 Mn 0.05 O2 is assembled into an all-solid-state lithium metal battery, or, the same electrolyte-gradient conductive interface protection layer-lithium metal structure is constructed on the other side of the electrolyte sheet Li6PS5Cl, that is, assembled into a lithium metal symmetric battery.

[0141] Figure 1 This is a schematic diagram of the all-solid-state lithium metal battery electrolyte-gradient conductive interface protection layer-lithium metal / lithium-free negative electrode structure of the present invention. An interface layer with certain conductive properties is added between the electrolyte and the lithium metal negative electrode. Due to the lithium-phobicity and electrochemical inertness of the electrolyte itself, it has ultra-high stability during the deintercalation process of metallic lithium and can maintain the integrity of the skeleton. Due to the difference in electronic conductivity of the interface layer, it not only ensures electron transmission, but also can effectively induce the uniform nucleation process of metallic lithium on the interface layer.

[0142] Figure 2The SEM and EDS images of the cross-section of the all-solid-state lithium metal battery electrolyte-gradient conductive interface protection layer-lithium metal structure in Example 1 successfully prepared a uniformly distributed interface layer, which helps to homogenize the electrolyte electric field and achieve the purpose of inhibiting the nucleation and growth of lithium dendrites. Figure 2 It can be seen that the C element is evenly distributed in the interface layer between the electrolyte and lithium metal, which indicates that the distribution of Super P in the interface layer is highly uniform. The successful preparation of a uniform and stable interface layer is beneficial to the uniformity of the electric field and potential distribution in the interface layer, thereby inducing uniform deposition of metallic lithium in the interface layer and achieving the goal of inhibiting the growth of dendrites inside the electrolyte.

[0143] Figure 3 The figure is a comparison chart of the battery cycle performance of Example 1 and Comparative Example 1. After 200 h of cycling, the polarization voltage of the lithium symmetric battery of Example 1 is significantly lower than that of Comparative Example 1. The full battery assembled in Example 1 can reach a discharge capacity of 111.5 mAh / g at 1 C, which is higher than that of Comparative Example 1, showing higher discharge capacity and cycle stability. It can be seen that compared with the comparative example, the electrolyte-gradient conductive interface protective layer-lithium metal structure constructed by the conductive interface protective layer in this embodiment has a certain promoting effect on the stability and improvement of the performance of the all-solid-state lithium metal battery.

[0144] Figure 4 The figure is a comparison of the battery cycle performance of Example 2 and Comparative Example 1. After 200 h of cycling, the lithium symmetric battery of Example 1 always maintains a stable and low polarization voltage, and the discharge capacity of the assembled full battery can still reach 120 mAh / g at 1 C, showing a high cycle stability performance. This further illustrates the role of the gradient conductive interface protection layer in homogenizing the electric field and improving the battery cycle stability performance.

[0145] Figure 5 The figure is a comparison chart of the battery cycle performance of Example 3 and Comparative Example 1. After 200 h of cycling, the polarization voltage of the lithium symmetric battery of Example 1 is further reduced, and the initial discharge capacity of the assembled full battery at 1 C can reach 143 mAh / g, indicating that Example 3 has a good optimization effect on the gradient conductive interface protection layer, and plays a positive role in homogenizing the electric field and improving the battery cycle stability performance.

[0146] It can be seen from the above embodiments that the present invention obtains an interface layer with gradient conductivity by evenly dispersing the electrolyte and the conductive carbon / lithium-philic metal, and constructs an electrolyte-gradient conductive interface protection layer-lithium metal / lithium-free negative electrode structure to take into account both structural stability and high electrochemical properties. Among them, the electrolyte has the characteristics of lithium repellency and electrochemical inertness, and has ultra-high stability during the insertion / deinsertion process of lithium; the difference in electronic conductivity of the interface layer of the conductive carbon / lithium-philic metal structure not only ensures electron transmission, but also can effectively induce the uniform nucleation process of metallic lithium on the interface layer, ultimately improving the battery performance. The process of the present invention is simple and easy to apply industrially, and the design of the electrolyte-gradient conductive interface protection layer-lithium metal / lithium-free negative electrode structure takes into account the structural stability and high electrochemical performance when it is subsequently applied to the battery.

[0147] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0148] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0149] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. An all-solid-state lithium metal battery interface protection layer, characterized in that: The interface protection layer is a single-layer structure or a multi-layer structure; The single-layer structure is composed of Li6PS5Cl and conductive carbon, and the mass ratio of Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5; Alternatively, the single-layer structure is composed of Li6PS5Cl and a lithium-philic element M, and the mass ratio of Li6PS5Cl to the lithium-philic element M is 75:25; The multilayer structure is formed by stacking several interface layers, the interface layer is composed of Li6PS5Cl and conductive carbon, and the mass ratio of Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5; In the several interface layers, the content of the conductive carbon increases layer by layer.

2. The all-solid-state lithium metal battery interface protection layer according to claim 1, characterized in that: The thickness of the interface protection layer is 5 to 200 μm.

3. The all-solid-state lithium metal battery interface protection layer according to claim 1, characterized in that: The conductive carbon comprises at least one of graphite, Super P, carbon nanotubes, carbon black and Ketjen black; The lithium-philic element M is at least one of Cu, Zn, Mg, Al, Sb, Ca, Ba, Ag, In, Bi, Ge, B and Sn.

4. A method for preparing an interface protection layer for an all-solid-state lithium metal battery according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The solid electrolyte Li6PS5Cl and the conductive carbon are mixed and ground under an inert atmosphere to obtain a mixture A, wherein the mass ratio of the Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5; Alternatively, the solid electrolyte Li6PS5Cl and the lithium-philic element M are mixed in a mass ratio of 75:25 under an inert atmosphere and then ground to obtain a mixture B; coating or depositing the mixture A or the mixture B on the surface of a substrate to obtain a single-layer structure; Alternatively, a plurality of the mixtures A having different conductive carbon contents are coated or deposited layer by layer on the substrate surface in order from low to high conductive carbon contents to obtain a multilayer structure.

5. The method for preparing an interface protective layer for an all-solid-state lithium metal battery according to claim 4, characterized in that: The particle size of the particles in the mixture A is 1 to 5 μm; The particle size of the particles in the mixture B is 1 to 5 μm; The conductive carbon comprises at least one of graphite, Super P, carbon nanotubes, carbon black and Ketjen black; The lithium-philic element M is at least one of Cu, Zn, Mg, Al, Sb, Ca, Ba, Ag, In, Bi, Ge, B and Sn.

6. The method for preparing an interface protective layer for an all-solid-state lithium metal battery according to claim 4, characterized in that: The coating or depositing of the mixture A or the mixture B on the surface of the substrate to obtain a single-layer structure specifically includes: The mixture A or the mixture B is coated on the surface of a substrate, and then a pressure of 300 to 500 MPa is applied to obtain a single-layer structure; Alternatively, the mixture A or the mixture B is attached to the surface of a substrate by atomic layer deposition to obtain a single-layer structure; The method of coating or depositing the plurality of mixtures A with different conductive carbon contents on the substrate surface layer by layer according to the conductive carbon contents from low to high to obtain a multilayer structure specifically includes: The plurality of mixtures A having different conductive carbon contents are coated layer by layer on the surface of the substrate according to the conductive carbon content from low to high, and then a pressure of 300 to 500 MPa is applied to obtain a multilayer structure; Alternatively, a plurality of the mixtures A having different conductive carbon contents are deposited layer by layer on the substrate surface in order from low to high conductive carbon contents to obtain a multilayer structure.

7. An electrolyte-gradient conductive interface protection layer-lithium metal structure, characterized in that: The electrolyte-gradient conductive interface protection layer-lithium metal structure comprises an electrolyte sheet, a lithium foil and an all-solid-state lithium metal battery interface protection layer as described in any one of claims 1 to 3; The electrolyte sheet and the lithium foil are respectively attached to two sides of the interface protection layer; When the interface protection layer is a multi-layer structure, the side of the multi-layer structure with a high conductive carbon content is attached to the lithium foil.

8. The method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure according to claim 7, characterized in that: The preparation method comprises: The solid electrolyte Li6PS5Cl and the conductive carbon are mixed and ground under an inert atmosphere to obtain a mixture A, wherein the mass ratio of the Li6PS5Cl to the conductive carbon is any one of 99.5:0.5, 99:1, 97:3 and 95:5; Alternatively, the solid electrolyte Li6PS5Cl and the lithium-philic element M are mixed in a mass ratio of 75:25 under an inert atmosphere and then ground to obtain a mixture B; The solid electrolyte Li6PS5Cl is pressed into an electrolyte sheet in a battery mold; The mixture A is coated or deposited on one side or both sides of the electrolyte sheet, and pressed to fit with the lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure; Alternatively, a plurality of the mixtures A with different conductive carbon contents are coated or deposited layer by layer on one or both sides of the electrolyte sheet according to the conductive carbon contents from low to high, and pressed and laminated with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure; Alternatively, the mixture B is coated or deposited on one or both sides of the electrolyte sheet, pressed and laminated with lithium foil, and then allowed to stand at 60±1° C. for 12±0.5 h to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure.

9. The method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure according to claim 8, characterized in that: The particle size of the particles in the mixture A is 1 to 5 μm; The particle size of the particles in the mixture B is 1 to 5 μm; The thickness of the electrolyte sheet is 800-900 μm; The conductive carbon comprises at least one of graphite, Super P, carbon nanotubes, carbon black and Ketjen black; The lithium-philic element M is at least one of Cu, Zn, Mg, Al, Sb, Ca, Ba, Ag, In, Bi, Ge, B and Sn.

10. The method for preparing an electrolyte-gradient conductive interface protection layer-lithium metal structure according to claim 8, characterized in that: The mixture A is coated or deposited on one side or both sides of the electrolyte sheet, and pressed to fit with the lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure, specifically comprising: The mixture A is coated or deposited on one side or both sides of the electrolyte sheet, and then a pressure of 300-500 MPa is applied, and then a pressure of 5-10 MPa is applied to laminate with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure; The method comprises coating or depositing the plurality of mixtures A with different conductive carbon contents on one side or both sides of the electrolyte sheet layer by layer according to the conductive carbon contents from low to high, and laminating the electrolyte sheet with the lithium foil under pressure to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure, specifically comprising: The plurality of mixtures A with different conductive carbon contents are coated or deposited layer by layer on one side or both sides of the electrolyte sheet according to the conductive carbon content from low to high, and then a pressure of 300-500 MPa is applied, and then a pressure of 5-10 MPa is applied to laminate with lithium foil to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure; The mixture B is coated or deposited on one side or both sides of the electrolyte sheet, pressed and laminated with lithium foil, and then left to stand at 60±1° C. for 12±0.5 h to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure, specifically comprising: The mixture B is coated or deposited on one or both sides of the electrolyte sheet, and then a pressure of 300-500 MPa is applied, and then a pressure of 5-10 MPa is applied to fit the lithium foil, and then the mixture is allowed to stand at 60±1°C for 12±0.5 h to obtain an electrolyte-gradient conductive interface protection layer-lithium metal structure.

11. An electrolyte-gradient conductive interface protection layer structure, characterized in that: The electrolyte-gradient conductive interface protection layer structure comprises an electrolyte sheet and an all-solid-state lithium metal battery interface protection layer as described in any one of claims 1 to 3; The interface protection layer is attached to one side of the electrolyte sheet; When the interface protection layer is a multi-layer structure, the side of the multi-layer structure with a low conductive carbon content is attached to the electrolyte sheet.

12. Use of an all-solid-state lithium metal battery interface protection layer as claimed in any one of claims 1 to 3 in the preparation of an all-solid-state lithium metal battery.

13. Use of an electrolyte-gradient conductive interface protection layer-lithium metal structure as claimed in claim 7 in the preparation of an all-solid-state lithium metal battery.

14. Use of an electrolyte-gradient conductive interface protection layer structure as claimed in claim 11 in the preparation of an all-solid-state lithium metal battery.

Citation Information

Patent Citations

  • Modification method for improving stability of lithium negative electrode of all solid state battery

    CN108923022A

  • Metal lithium negative electrode, preparation method thereof and lithium battery

    CN110707287A

  • Composite metal lithium negative electrode, preparation method thereof, lithium secondary battery and device

    CN115461891A

  • Composite negative electrode, preparation method thereof and lithium ion battery

    CN115775863A

  • Negative pole piece, preparation method of negative pole piece, and secondary battery, battery module, battery pack and electric device comprising negative pole piece

    CN116438675A